BENTUK DAN MAKNA UNGKAPAN PANTANG LARANG KOMUNITAS ADAT DESA KARANG PANDAN KECAMATAN PAKISAJI KABUPATEN MALANG DALAM SEBUAH PENAFSIRAN HERMENUTIKA BUDAYA - Eka Ratmawati (JURNAL ILMIAH BAHASA DAN SASTRA, 2017)
Society is bunch of individuals that have the same backgrounds and characteristics based on their environments, then make a culture. The culture is reflection of the society’s life such as job, religion, knowledge and culture that is formed by people’s belief. Belief that is passed down from generation to generation written or verbally is called folklore. Such as Javanese myth, is story that tells about Javanese’s belief to sacred things. Myth is one of oral traditions, basically not too different with Javanese’s written tradition. Myth or pamali means warning that ancient people used. The warning that comes from generation to generation is often heard from the old people, such as grandpas and grandmas. Keyword: myth, form, mean